Wearable Sensor-Based Biofeedback Training for Balance and Gait in Parkinson Disease: A Pilot Randomized Controlled Trial - Carpinella, Ilaria; Cattaneo, Davide; Bonora, Gianluca; Bowman, Thomas; Martina, Laura; Montesano, Angelo; Ferrarin, Maurizio (Archives of physical medicine and rehabilitation, 2017)
To analyze the feasibility and efficacy of a novel system (Gamepad [GAMing Experience in PArkinson's Disease]) for biofeedback rehabilitation of balance and gait in Parkinson disease (PD). Randomized controlled trial. Clinical rehabilitation gym. Subjects with PD (N=42) were randomized into experimental and physiotherapy without biofeedback groups. Both groups underwent 20 sessions of training for balance and gait. The experimental group performed tailored functional tasks using Gamepad. The system, based on wearable inertial sensors, provided users with real-time visual and acoustic feedback about their movement during the exercises. The physiotherapy group underwent individually structured physiotherapy without feedback. Assessments were performed by a blinded examiner preintervention, postintervention, and at 1-month follow-up. Primary outcomes were the Berg Balance Scale (BBS) and 10-m walk test (10MWT). Secondary outcomes included instrumental stabilometric indexes and the Tele-healthcare Satisfaction Questionnaire. Gamepad was well accepted by participants. Statistically significant between-group differences in BBS scores suggested better balance performances of the experimental group compared with the physiotherapy without biofeedback group both posttraining (experimental group−physiotherapy without biofeedback group: mean, 2.3±3.4 points; P=.047) and at follow-up (experimental group−physiotherapy without biofeedback group: mean, 2.7±3.3 points; P=.018). Posttraining stabilometric indexes showed that mediolateral body sway during upright stance was significantly reduced in the experimental group compared with the physiotherapy without biofeedback group (experimental group−physiotherapy without biofeedback group: −1.6±1.5mm; P=.003). No significant between-group differences were found in the other outcomes. Gamepad-based training was feasible and superior to physiotherapy without feedback in improving BBS performance and retaining it for 1 month. After training, 10MWT data were comparable between groups. Further development of the system is warranted to allow the autonomous use of Gamepad outside clinical settings, to enhance gait improvements, and to increase transfer of training effects to real-life contexts.